A simple numerical approach for the pushover analysis of slender cantilever bridge piers taking into account geometric nonlinearity - Di Re, Paolo; Bernardini, Davide; Ruta, Daniela; Paolone, Achille (Asian journal of civil engineering. Building and housing, 2022)
The response of slender bridge piers to horizontal actions may be significantly influenced by geometric nonlinearities. In such conditions, the use of sophisticated models implemented in complex structural analysis software can be economically disadvantageous, especially in the preliminary design phases. This paper proposes a simple numerical procedure to compute the nonlinear pushover response of cantilever bridge piers subject to horizontal loads. The procedure is based on an iterative approach to enforce the element equilibrium under large displacements, efficiently accounting for P-Delta effects induced by vertical loads. Evaluation of the bending moment–curvature response of the pier base cross section is required and used as basic input data. For fast preliminary analyses, sectional response can be manually computed in simplified linearized form, thus completely eliminating the need to use structural analysis software. Indeed, the entire procedure can be implemented in standard programming codes, such as Python TM or Matlab ® , and used to evaluate the pushover response of piers with arbitrary cross section. Comparison with experimental test results and solutions based on Finite Element models shows that proposed procedure can be used to get a fast, yet accurate, estimate of the entire force–displacement curve and, in particular, of the pier ultimate displacement.